Implemetasi Metode Fuzzy AHP (Analitycal Hierarchy Process) - COPRAS (Complex Proportional Assessment) untuk Rekomendasi Penentuan Kelompok Tani Terbaik (Studi Kasus : Dinas Pertanian Kabupaten Bangkalan) - Rachmad Faqih Santoso; Nurul Hidayat; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Agricultural development can be done by forming an institution that functions as a forum for information and learning about agriculture to farmers, one of which is by forming farmer groups. But there are some farmer groups that are often abused. This condition has an impact on the development of farmer groups that tend to decline from year to year. Efforts to foster and empower these farmer groups must also be adjusted to technological progress and demands on the application of agricultural development programs. Therefore in this study the method used is the Implementation of the Fuzzy AHP (Analitycal Hierarchy Process) - COPRAS (Complex Proportional Assessment) Method. The Fuzzy AHP method is considered more accurate in weighting criteria than the AHP method. And the COPRAS method is more accurate in calculating alternative ranking because the evaluation of maximum and minimum criteria is done separately. Based on the results of the implementation of the AHP (Analitycal Hierarchy Process) - Copras (Complex Proportional Assessment) method for the recommendation to determine the best farmer group, it has an accuracy rate of 68% (using 25 data) and 48% (using 50 data). And having the same interpretation coefficient of correlation has a close to perfect relationship (Ï> 0.9). This shows that this method is able to help and make decisions.